Short-Chain Carboxylic-Acid-Stimulated, PMN-Mediated Gingival Inflammation - Niederman, Richard; Jie Zhang; Kashket, Shelby (Critical reviews in oral biology and medicine, 1997)
This communication reviews the effects of short-chain carboxylic acids on human cells of importance to the periodontium. The central hypothesis is that these acids can alter both cell function and gene expression, and thus contribute to the initiation and prolongation of gingival inflammation. Short-chain carboxylic acids [CH3-(CH2)x-COOH, x < 3] are metabolic intermediates with a broad range of apparently paradoxical biological effects. For example, lactic acid (CH3-CHOH-COOH), a 3-carbon alpha-hydroxy-substituted acid, is widely recognized for its cariogenicity. Lactic acid, however, also occurs in tropical fruits, and is the active ingredient in a variety of anti-wrinkle creams developed by dermatologists. In marked contrast, the unsubstituted 3-carbon propionic acid (CH 3 -CH 2 -COOH) is used as a food preservative and is the active principle for one class of non-steroidal anti-inflammatory agents. Interestingly, the addition of one carbon to propionic acid dramatically changes the biological effects. The unsubstituted 4-carbon butyric acid (CH3-CH2-CH2-COOH) is used by hematologists as a de-differentiating agent for the treatment of sickle cell anemia, but by oncologists as a differentiating agent for cancer chemotherapy. Finally, acting either individually or in concert, these acids can increase vascular dilation. Clearly, these acids, while metabolically derived, have a number of very divergent activities which are cell-type-specific (Fig. 1). It may be telling that periodontal bacteria produce these acids in millimolar concentrations, and that these bacteria can be characterized by their acid production profiles. It is no less interesting that these acids occur in the gingival crevices of human subjects with severe periodontal disease at millimolar levels which are > 10-fold higher than those found in mildly diseased subjects, and are undetectable in healthy subjects. Further, when applied directly to healthy human gingiva, short-chain carboxylic acids stimulate a gingival inflammatory response and inflammatory cytokine release. At the cellular level, these acids inhibit proliferation of gingival epithelial and endothelial cells, and inhibit leukocyte apoptosis and function, but can stimulate leukocyte cytokine release. At the molecular level, these acids can stimulate neutrophil gene transcription, translation, and protein expression. Thus, the likelihood is high that these acids, in addition to their cariogenic activity, can promote and prolong gingival inflammation. Our challenge will be to identify the cell or cells of the periodontium which respond to short-chain carboxylic acids, to delineate their responses and the molecular mechanism(s) of these effects, and to categorize the aspects of the inflammatory components which damage and those which protect the host. With this information, it may be possible to begin to rationally identify and test pharmaceutical agents which diminish the harmful aspects, while enhancing the beneficial components, of the inflammatory response.